Collaborative Learning in Higher Education: Bibliometrics Analysis - Suwandi, Sahri; Baron, Rifari; Sanjaya, Ricky Eka; Hadie, Irfan; Fidinillah, Mildan Arsdan; Gufron, Uup; Saputri, Nia Liska; Purwanto, Andri (Universitas Muhammadiyah Mataram, 2025)
The importance of collaborative learning in higher education cannot be overlooked, as it plays a crucial role in enhancing student engagement, academic achievement, and collaborative skills. Based on existing literature, collaborative learning has increasingly been recognized as an effective pedagogical approach in higher education contexts. This study conducts a comprehensive bibliometric analysis to examine the development, structure, and research trends of collaborative learning in higher education over the period 2014–2023. The dataset was retrieved from the Scopus database and consists of peer-reviewed publications focusing on collaborative learning within higher education settings. The bibliometric analysis reveals several key findings, including a steady growth in publication output, with a significant increase observed after 2020 and the highest number of publications recorded in 2023. The results also indicate that research productivity is concentrated among a limited number of prolific authors and institutions, while the majority of authors contributed only a single publication. In addition, a small number of highly cited articles exert substantial influence on the field, particularly those published in high-impact educational technology journals. The dominance of Social Sciences and Computer Science as subject areas highlights the interdisciplinary nature of collaborative learning research, emphasizing both pedagogical and technological perspectives. Overall, this study provides a comprehensive overview of the scientific landscape of collaborative learning in higher education, maps its intellectual structure, and offers insights into future research directions in this field.